2012
DOI: 10.5267/j.msl.2012.04.022
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis on the adoption of electronic banking in the financial institutes using structural, behavioral and contextual factors

Abstract: This research examines contextual, structural and organizational factors, which can facilitate or slow down adoption of innovation in Electronic Banking in the financial Institutions. Threedimensional model co-structure, co-behavioral, contextual (3C) is used in this research. This schema is a logical model in the categories of models and many of concepts, events and organizational phenomena can be examined. Structural factors including type of the organization of institution, work distribution, preparing mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Theories Unit of analysis (Questionnaire) Results Yu and Asgarkhani (2015), Arayesh (2015), Ahmadi and Afrouzi (2012) The results confirmed that all the weights associated with the service channel fit (SCF) were statistically significant. Aderonke A and Charles K (2010), Jalal, Marzooq and Nabi (2011), Abadi and Nematizadeh (2012), Moga, Nor and Mitrica (2012), Raida and Néji (2013), Alikhani and Davarzani (2014), Mansour, Eljelly and Abdullah (2016), Rodrigues, Oliveira and Costa (2016).…”
Section: Authors and Yearsupporting
confidence: 53%
See 3 more Smart Citations
“…Theories Unit of analysis (Questionnaire) Results Yu and Asgarkhani (2015), Arayesh (2015), Ahmadi and Afrouzi (2012) The results confirmed that all the weights associated with the service channel fit (SCF) were statistically significant. Aderonke A and Charles K (2010), Jalal, Marzooq and Nabi (2011), Abadi and Nematizadeh (2012), Moga, Nor and Mitrica (2012), Raida and Néji (2013), Alikhani and Davarzani (2014), Mansour, Eljelly and Abdullah (2016), Rodrigues, Oliveira and Costa (2016).…”
Section: Authors and Yearsupporting
confidence: 53%
“…However, there are several theories and models in literature which have been employed to explain the relationships between the factors affecting the acceptance and adoption dominancy and user's attitude and willingness as shown in Appendix (1). Among them, there are three very well-known models which are the following: Technology Acceptance Model (TAM) by (Davis in 1989, Poon (2007), Aderonke A and Charles K. (2010), ), Jalal et al (2011), Johar and Awalluddin (2011, Abadi and Nematizadeh (2012), Ahmadi and Afrouzi (2012), Moga, et al (2012), Raida and Néji. (2013), El-Qirem (2013), Sanayei and Saneian (2013), Alikhani and Davarzani.…”
Section: The Applied Theories and Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the area of energy prediction, the artificial neural network technique is well-known for the accurate forecasting of energy usage [29]. However, there is a challenging issue related to accuracy when the scale is reduced (e.g., neighborhood or household level) although precise load forecasting is possible at the aggregated level (e.g., national level), In this vein, the study of Ahmadi [48] suggests that the artificial neural network is developed in as many as 40% of the energy artificial neural networking algorithms [49].…”
Section: Artificial Intelligence (Ai) Application In Smart Grids and mentioning
confidence: 99%